Spatial Variation in Excess Mortality in Mexico during the First 2 Years of the COVID-19 Pandemic - Christian Sánchez-Carrillo; Giovanna Santana Castañeda; Marcela Virginia Santana Juárez; Emmanuelle Quentin (Advances in Public Health)
Background. Excess mortality from all causes is a reliable indicator of the direct or indirect effect of the COVID-19 pandemic. This study aimed to estimate excess deaths in Mexico during the first 2 years of the COVID-19 pandemic and to examine the spatial and temporal variations in relative excess mortality at the subnational level. Materials and Methods. This ecological study was based on publicly available governmental data and compared 2020–2021 total deaths with the average number of deaths in 5 previous years. The relative excess mortality was then analyzed as a function of time (waves) and space (distribution maps). Results. Between January 1, 2020 and December 31, 2021, Mexico recorded 2,136,611 deaths out of 1,385,240 expected deaths, representing 751,371 excess deaths (95% CI: 709,948.267–792,793.732). During this period, we identified three waves of excess deaths, the second being the most severe, with 109,846 more deaths than expected. When examining each wave, spatial variation in relative excess mortality was identified, with all 32 states experiencing more deaths than expected (values > 0%). However, in Mexico City, Tlaxcala and Queretaro recorded values greater than 100% at different times. Conclusions. During the first 2 years of the COVID-19 pandemic (2020–2021), the number of deaths increased excessively in the 32 states. The spatial variation in relative excess mortality in each observed wave demonstrated that the response to the effects of the pandemic in Mexico differed due to various factors, such as prevention measures against COVID-19, the beginning of the vaccination campaign, and pandemic fatigue which caused a certain relaxation and therefore a return of tourism, mainly in coastal areas. Therefore, it is necessary to implement equitable policies for the care of particularly affected areas.